(untitled) (Journal of Hama University, 2022)
The study aimed at assessing the content of Arabic language book according to the language immersion standards needed to be available in educational courses. The study adopted the descriptive approach. Its sample consisted of books teaching Arabic at the lower _intermediate level, at the Higher Institute of Languages ​​in Damascus, A list of controlled criteria was used. By using appropriate statistical methods, the study reached a conclusion which showed that: the degree of availability of standards in the book of the lowest -intermediate is low on both the domains of creative and critical self-learning, and the language partner and participation, while it was great on the domain of functional and life. Finally, the research recommended adopting linguistic immersion standards when developing Arabic language teaching curricula, and building an Arab frame of reference for teaching Arabic as a second language that takes into account the linguistic and cultural immersion standards and includes them at all levels.